Recurrent tubercular lymphadenitis in an HIV-positive hospital sanitation worker: a clinicosocial case report - S., Arya T. (International Journal Of Community Medicine And Public Health, 2026)
Tuberculosis (TB) remains one of the leading opportunistic infections among people living with HIV, particularly in low- and middle-income countries. Extrapulmonary tuberculosis (EPTB), especially tubercular lymphadenitis, is more common among immunocompromised individuals and may present with recurrent disease, diagnostic difficulties, and prolonged treatment requirements. We report the case of a 26-year-old HIV-positive male hospital sanitation worker who developed recurrent bilateral infraclavicular tubercular lymphadenitis with cold abscess formation despite regular antiretroviral therapy (ART) and anti-tubercular treatment (ATT). The patient belonged to a socioeconomically vulnerable background with undernutrition, overcrowded housing, and probable occupational exposure to infectious material. Investigations including FNAC, ultrasonography, and CBNAAT confirmed drug-sensitive tubercular lymphadenitis. The patient demonstrated good adherence to both ART and ATT but experienced recurrent episodes requiring prolonged management under the National Tuberculosis Elimination Programme (NTEP). This case highlights the complex interaction between HIV infection, occupational vulnerability, undernutrition, and adverse social determinants contributing to recurrent extrapulmonary tuberculosis. Strengthening occupational safety measures, nutritional support, and integrated HIV-TB care is essential for vulnerable healthcare-associated workers.